COMPUTED TOMOGRAPHIC SCANS OF BRAINS IN ACCIDENTAL AND EMERGENCY PATIENTS AT SAPPASITTHIPRASONG HOSPITAL; A RETROSPECTIVE STUDY OF THE INDICATIONS AND FINDINGS. - SASTIWANAPONG, Sittiporn; SNITWONGSE NA AYUDHYA, Nitaya; LOWANITCHAI, Somrak (The ASEAN Journal of Radiology, 2023)
The requisition for computed tomographic (CT) scan of brain had been increasing continually each year at Sappasitthiprasong Hospital. In 2006, 80% of them were sent from Accident-Emergency Division, most of them were in a condition of Glasgow Coma Scale (GCS) score, of 15. (table 1) The retrospective studied were performed by reviewing the medical records and the CT brain scans of both the traumatic and the non-traumatic groups. (table 2) The demographic data, GCS score and clinical symptoms or indications were collected to observe the prevalence of negative and positive CT findings in order to determine the indications that are favorable correlated with positive CT findings in acute traumatic head injuries with GCS 15. There were totally 454 patients, included with an average of 43.08±13.30 years, male 69.16%. The numbers of positive findings were more than that of the negative ones in the non-traumatic cases and traumatic cases with GCS less than 14. Where as in the 243 traumatic cases, only 84 had positive CT brain scan findings, of which 14 cases or 10.7% were the cases with GCS score of 15. In this group the indications that significantly constituted positive CT findings were headache, sign of basal skull fracture, skull crown fracture, nausea, vomiting, drowsiness and amnesia, respectively. This study agreed with particular indications that could limit the use of CT scan without underestimating the lesions at particular setting.